Configuring Anion‐Exchange Membranes for High Conductivity and Alkaline Stability by Using Cationic Polymers with Tailored Side Chains. Issue 10 (29th February 2016) - Jannasch, Patric; Weiber, Eva Annika
Abstract : Polymeric anion‐exchange membranes (AEMs) are critical components for alkaline membrane fuel cells (AMFCs) which offer several attractive advantages including the use of platinum‐free catalysts and a wide choice of fuel. The development of AMFCs and other electrochemical energy systems is currently severely limited by the lack of AEMs with sufficient alkaline stability. Still, significant advances have been made in recent years and one of the most promising approaches to emerge is the design and synthesis of cationic polymers with various side chain arrangements. Especially, synthetic strategies where the cationic ion‐exchange groups are placed on pendant alkyl spacer chains along the backbone seem to significantly improve microphase separation, hydroxide ion conductivity, and alkaline stability in relation to standard AEMs with cations placed in benzylic positions directly on the backbone. This article reviews recent approaches to high‐performance cationic membrane polymers involving different side chain designs, and discusses some possible future directions. Abstract : Polymeric anion‐exchange membranes are crucial components in alkaline membrane fuel cells and other electrochemical energy systems. Recent results show that both OH − conductivity and alkaline stability of these materials are significantly enhanced by introducing flexible and hydrolytically stable alkyl side chains in the macromolecular design. Here, the latest trends in this research area are briefly reviewed.